Analysis of the Mathematical Reasoning Ability of Grade 8th Students on Triangular Materials - Nasution, Elvi Leila Suheila; Angraini, Lilis Marina; Widiati, Indah; Amelia, Sindi (EDUPEDIA Publisher, 2024)
One of the basic skills in mathematics education is mathematical reasoning, which is essential to help students acquire the critical and logical thinking skills they will need in the future, especially in understanding and solving geometric difficulties such as the idea of triangles. This research is qualitative descriptive research that aims to describe the mathematical reasoning ability of grade VIII students of SMP Negeri 25 Pekanbaru. The data collection technique in this study is in the form of a description test instrument of 6 questions and interviews. Data analysis techniques are carried out by data reduction, data presentation and conclusions. Based on the results of the study, it was obtained that the average mathematical reasoning ability of students was 45.50% with a fairly good category. The highest indicator of reasoning ability is the ability to perform calculations based on certain rules or formulas of 94% with very good criteria. The lowest indicator of reasoning ability is in the indicator of checking the validity of an argument of 23% with a low criterion.